2012
DOI: 10.1152/ajpgi.00313.2012
|View full text |Cite
|
Sign up to set email alerts
|

Tissue remodeling in eosinophilic esophagitis

Abstract: Eosinophilic esophagitis (EoE) is a recently recognized, immune-mediated disease characterized clinically by symptoms of esophageal dysfunction and histologically by eosinophil-predominant inflammation. The chronic esophageal eosinophilia of EoE is associated with tissue remodeling that includes epithelial hyperplasia, subepithelial fibrosis, and hypertrophy of esophageal smooth muscle. This remodeling causes the esophageal rings and strictures that frequently complicate EoE and underlies the mucosal fragility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 177 publications
(199 reference statements)
2
99
0
5
Order By: Relevance
“…EoE is characterized by basal cell hyperplasia and subepithelial fibrosis (53). We propose that follistatin inhibits BMP activities during disease progression, thereby blocking the differentiation of basal progenitor cells.…”
Section: Nox4mentioning
confidence: 97%
See 1 more Smart Citation
“…EoE is characterized by basal cell hyperplasia and subepithelial fibrosis (53). We propose that follistatin inhibits BMP activities during disease progression, thereby blocking the differentiation of basal progenitor cells.…”
Section: Nox4mentioning
confidence: 97%
“…In the esophagus, basal cells serve as progenitor cells to maintain the stratified squamous epithelium (2,3). Disruption of the balance of basal cell activities underlies multiple pathological conditions, including eosinophilic esophagitis (EoE), in which basal cells become hyperplastic in the setting of high levels of the inflammatory cytokines eotaxin-3, IL-5, and IL-13 (4)(5)(6). Studies have shown that these hyperplastic basal cells serve as an important source of cytokines and chemokines that facilitate EoE disease progression (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…These processes lead to sub epithelial fibrosis and alternation in smooth muscle contraction, which in result in the rings and strictures seen on endoscopy and the dysphagia experienced by patients [47].…”
Section: Immune-mediated Responsementioning
confidence: 99%
“…It is believed that the mechanism in which EoE occurs is by food or environmental allergens contacting a possible leaky esophageal epithelium and triggering a T-helper 2 (Th2) cell-mediated immune response (involving interleukin [IL]-4, IL-5, IL-9 and IL-13). This response stimulates the epithelium to produce eotaxin-3, a potent chemokine that recruits eosinophils, which promotes local inflammation, injury, and tissue remodeling via increased expression of transforming growth factor (TGF)-β1 leading to smooth muscle dysfunction [22][23][24].…”
Section: Pathogenesismentioning
confidence: 99%